Perlindungan Konsumen terhadap Pasien Klinik Kecantikan oleh Dokter Gadungan Ditinjau dari Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen (UUPK) - Amir Khoiruddin; Fritta Omea Mellenia; Gita Mardiana Agesti; Elza Savira Chairani Zakaria (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the legal protection of consumers who are victims of fake doctors from the perspective of UUPK and its relation to malpractice. This research method is normative juridical with a statutory and conceptual approach. The results of the study indicate that patients who suffer losses due to the actions of fake doctors can claim compensation based on Article 19 of UUPK and file a civil or criminal lawsuit for alleged malpractice. In addition, fake doctors can be subject to criminal sanctions in accordance with Article 62 of UUPK and the Medical Practice Law. However, there are still obstacles in law enforcement, especially in the supervision of licensing of medical personnel in beauty clinics. Therefore, strengthening regulations and supervision is needed.